2011
DOI: 10.1186/1745-6150-6-54
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis reveals wide distribution of globin X

Abstract: The vertebrate globin gene repertoire consists of seven members that differ in terms of structure, function and phyletic distribution. While hemoglobin, myoglobin, cytoglobin, and neuroglobin are present in almost all gnathostomes examined so far, other globin genes, like globin X, are much more restricted in their phyletic distribution. Till today, globin X has only been found in teleost fish and Xenopus. Here, we report that globin X is also present in the genomes of the sea lamprey, ghost shark and reptiles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 23 publications
4
16
0
Order By: Relevance
“…The sequence analysis of GbX shows highest identity scores with neuroglobin (Ngb) (25-35%) (2,3,16) and suggests that phylogenetically they derive from the same common ancestor that diverged ∼800 million yr ago from the evolutionary branch of Hb, Mb, and cytoglobin (Cygb) (Fig. S1) (17).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sequence analysis of GbX shows highest identity scores with neuroglobin (Ngb) (25-35%) (2,3,16) and suggests that phylogenetically they derive from the same common ancestor that diverged ∼800 million yr ago from the evolutionary branch of Hb, Mb, and cytoglobin (Cygb) (Fig. S1) (17).…”
Section: Resultsmentioning
confidence: 99%
“…The function of these proteins remains largely unknown. Globin X (GbX) is a novel globin found in fish, amphibians, and reptiles that diverged early from a common ancestor to hemoglobin (Hb) and myoglobin (Mb) (2,3), thus representing a landmark in the evolution of the globins, probably carrying out functions that were later taken over by other globins in higher vertebrates. Because six-coordinate globins have proximal and distal histidines that bind the heme iron and are expressed at low concentrations, it has been hypothesized that they did not evolve for oxygen storage and transport, but rather participate in reactive oxygen and nitrogen species metabolism or other processes (1,4).…”
mentioning
confidence: 99%
“…The globin X ( GbX ) gene has been documented in the genomes of some cyclostomes, elasmobranchs, teleost fishes, amphibians, and reptiles (Dröge and Makalowski 2011; Roesner et al 2005). This gene encodes a membrane-bound, hexacoordinate globin that appears to perform an antioxidant function (Blank et al 2011b).…”
Section: The Functional Diversification Of Vertebrate Globinsmentioning
confidence: 99%
“…The most recent molecular phylogenetic analysis of globin sequences from the five □ S This article contains supplemental (19) demonstrated that the functional hexacoordinated Globin X (GbX) protein of the cypriniform adult zebrafish is located in the nervous central system and retina, suggesting a neural-based function but contradicting a previous result obtained from the other cypriniform Carassius auratus GbX showing that mRNA GbX was not detected in brain and eye but in other tissues (muscle, heart, gut, and liver) (20). Thought to be restricted to vertebrate, GbX-like sequences have been recently identified in silico in other deuterostomes and in protostomes, supporting an early emergence of this gene family in metazoan evolution (21).…”
mentioning
confidence: 99%